Utrecht work engagement scale: Construct validity and reliability in Chilean health science students - Rocio Glaria Lopez; Cristhian Perez Villalobos; Paulina Ortega Bastidas; Berta Schulz-Banares; Angela Pino-Zuniga (Journal of the Pakistan Medical Association, 2021)
Objective: provide new background in relation to the factor structure and reliability of the factors identified from the Utrecht Work Engagement Scale – Student (UWES-S) in students of health careers in Chile. Methods: A quantitative study with relational analytical scope was carried out, through a non-experimental cross-sectional design through a survey. 898 university students selected through non-probabilistic sampling by groups belonging to Medicine, Kinesiology, Pharmacy and Speech and language therapy. The students responded the UWES-S and a sociodemographic questionnaire. The total sample was randomly subdivided into two subsamples. With the first one, an Exploratory Factor Analysis was performed, using the method of extraction of the Main Axis Analysis. With the second one, a Confirmatory Factor Analysis was performed, using the maximum likelihood method and the following indices: Comparative Fit Index (CFI), Tucker-Lewis Index (TLI) and the Root Mean Square Error of Approximation (RMSEA). Also the Cronbach alpha reliability of each item was calculated. For data processing STATA 11 SE statistical package was used. Results: Kaiser-Guttman criterion and the Horn’s Parallel Analysis aimed to the existence of two factors called Involvement with studies and Enthusiasm for the career. CFI, TLI and RMSEA show that this is one of the solutions with best fit. Conclusion: Two factors were identified called Involvement with studies and Enthusiasm for the career. Neither the solution obtained nor the previous solutions showed an adequate adjustment to the data. The confirmatory factor analysis showed that this is one of the solutions with best fit. Continuous...